A High-Throughput Flow Cytometry Screen Identifies Molecules That Inhibit Hantavirus Cell Entry. (August 2018) - Buranda, Tione; Gineste, Catherine; Wu, Yang; Bondu, Virginie; Perez, Dominique; Lake, Kaylin R.; Edwards, Bruce S.; Sklar, Larry A.
Hantaviruses cause hemorrhagic fever with renal syndrome (HFRS) and hantavirus cardiopulmonary syndrome (HCPS), which infects more than 200, 000 people worldwide. Sin Nombre virus (SNV) and Andes virus (ANDV) cause the most severe form of HCPS, with case fatality ratios of 30%–40%. There are no specific therapies or vaccines for SNV. Using high-throughput flow cytometry, we screened the Prestwick Chemical Library for small-molecule inhibitors of the binding interaction between UV-inactivated and fluorescently labeled SNV R18 particles, and decay-accelerating factor (DAF) expressed on Tanoue B cells. Eight confirmed hit compounds from the primary screen were investigated further in secondary screens that included infection inhibition, cytotoxicity, and probe interference. Antimycin emerged as a bona fide hit compound that inhibited cellular infection of the major HCPS (SNV)- and HCPS (Hantaan)-causing viruses. Confirming our assay's ability to detect active compounds, orthogonal testing of the hit compound showed that antimycin binds directly to the virus particle and blocks recapitulation of physiologic integrin activation caused by SNV binding to the integrin PSI domain.